Insights into the Spatial and Temporal Variability of Soil Attributes in Irrigated Farm Fields and Correlations with Management Practices - Tomaz, Alexandra (2022)
Funding Information: This research is co-funded by the European Union through the European Regional Development Fund, included in the COMPETE 2020 (Operational Program Competitiveness and Internationalization) through Centro de Química (UIBD/00616/2020), funded by FCT—Fundação para a Ciência e a Tecnologia, Portugal, and through the FitoFarmGest Operational Group (PDR2020-101-030926). Publisher Copyright: © 2022 by the authors.